Characterization of two pterocarpan glycosyltransferases in Astragalus membranaceus and their application in whole-cell biocatalysis - Bai-Han Gao; Meng Zhang; Kuan Chen; Lin-Lin Wang; Ming-Ju Yao; Hong-Ye Li; Ming Xiong; Yu-Xi Huang; Yang Zhang; Quan-Li Liu; Juan Guo; Min Ye; et al. (Medicinal Plant Biology)
Pterocarpan glucosides are biologically active natural products, in which the glucosyl group plays an important role. However, specific pterocarpan glycosyltransferases have rarely been reported. In this study, two highly efficient glycosyltransferases, AmGT28 and AmGT44, from Astragalus membranaceus, catalyzing the conversion of medicarpin (1) to medicarpin 3-O-glucoside (1a) were identified. They could also use other pterocarpans and isoflavonoids as substrates, showing a preference for pterocarpans over isoflavonoids. A new isoflavone 7-O-glucoside 5a was prepared through a scaled-up enzymatic reaction. Furthermore, AmGT44 was expressed in E. coli to establish a whole-cell biocatalytic system (500 μL with 0.1 mM substrate), which could glucosylate pterocarpans 1-3 with a conversion rate of up to 100% and a titer of 30-38 μg/mL within 25 h. The titer of maackiain 3-O-glucoside (2a) could reach 78.66 μg/mL in a 10-mL system. The study provides efficient catalytic tools for the biosynthesis of pterocarpan glycosides.